2002
DOI: 10.1210/en.2002-220401
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Sensitive Phenotype in Mice Lacking Pituitary Adenylate Cyclase-Activating Polypeptide

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a highly conserved hormone. Targeted disruption of the PACAP gene has revealed a role for this peptide in lipid metabolism, carbohydrate metabolism, and the sympathetic response to insulin stress. We report here that PACAP null mice are temperature sensitive. When raised at 21 C, only 11% of the PACAP null mice survived past the first 2 wk after birth, but when raised at 24 C, most (76%) of the PACAP null mice survived. The question is the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
112
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 48 publications
3
112
1
Order By: Relevance
“…PACAP peptide, when administered to mice via the third ventricle, leads to a sharp reduction of food intake (Mizuno et al, 1998). Additionally, PACAP knock-out mice exhibit severe metabolic disorders, including impairments to thermogenesis and the counterregulatory response to hypoglycemia (Gray et al, 2001(Gray et al, , 2002. The VMH has been shown to play a role in both of these processes, suggesting that PACAP may contribute to some portion of these VMH functions (Perkins et al, 1981;Borg et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…PACAP peptide, when administered to mice via the third ventricle, leads to a sharp reduction of food intake (Mizuno et al, 1998). Additionally, PACAP knock-out mice exhibit severe metabolic disorders, including impairments to thermogenesis and the counterregulatory response to hypoglycemia (Gray et al, 2001(Gray et al, , 2002. The VMH has been shown to play a role in both of these processes, suggesting that PACAP may contribute to some portion of these VMH functions (Perkins et al, 1981;Borg et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that PACAP Ϫ/Ϫ mice present numerous phenotypes, including high mortality of PACAP Ϫ/Ϫ mice (37), inadequate heat production (38), reduction in glucose levels (39), and deficits in circadian light response (40). It is possible that these factors could influence testicular aging as well.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of the phenotypes reported so far in PACAP-or PAC1-deficient mice have been observed under paraphysiological conditions, such as metabolic stress after insulin injection [10,11] thermoregulatory stress [7] and septic shock following LPS injection [13]. These observations suggest that PACAP mainly acts as an emergency response factor to reinforce and sustain normal homeostatic mechanisms during prolonged periods of challenge to them.…”
Section: Discussionmentioning
confidence: 99%